2019
DOI: 10.1016/j.physletb.2018.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Non-strange dibaryons studied in the γd → π0π0d reaction

Abstract: Coherent double neutral-pion photoproduction on the deuteron, γd→π 0 π 0 d, has been experimentally studied at incident photon energies ranging from 0.75 to 1.15 GeV. The total cross section as a function of the γd center-of-mass energy shows resonance-like behavior, which peaks at approximately 2.47 and 2.63 GeV. The measured angular distribution of deuteron emission is rather flat, which cannot be reproduced by the kinematics of quasifree π 0 π 0 production with deuteron coalescence. In π 0 d invariant-mass … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Up to now, the dibaryon has been observed by WASA@COSY Collaborations in the process of and the fusion process of . It seems that was also observed in another process, at ELPH [29][30][31]. It should be stressed that the forthcoming experiments at anda (Pbar ANnihilation at DArmstadt) are expected to provide a confirmation of this dibaryon state if it does exist.…”
Section: Introductionsupporting
confidence: 53%
“…Up to now, the dibaryon has been observed by WASA@COSY Collaborations in the process of and the fusion process of . It seems that was also observed in another process, at ELPH [29][30][31]. It should be stressed that the forthcoming experiments at anda (Pbar ANnihilation at DArmstadt) are expected to provide a confirmation of this dibaryon state if it does exist.…”
Section: Introductionsupporting
confidence: 53%
“…The authors mention that " " has been observed in the and reactions. In fact, in [41,42], one can observe a deviation of the experimental cross section from the theoretical results reported by [43,44] at low photon energies. These calculations are based on the impulse approximation, and the π rescattering terms are neglected.…”
Section: Discussionmentioning
confidence: 71%
“…Let us further extend this discussion. The authors of [41,42] also studied the reaction [45,46]. This reaction was throughly studied theoretically in [47], and the authors discovered that the pion rescattering mechanisms were particularly important, and the most striking feature of the reaction, i.e., the shift of the shape of the invariant mass distributions, was well reproduced.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, the first report on data for the reaction also appeared, reaching in energy down to the region. The measurements conducted at ELPH, Japan, only reach down to the high-energy side of the region [55,56]. Measurements performed at MAMI even reach below the region [57].…”
Section: Electromagnetic Excitation Of (2380)mentioning
confidence: 99%
“…There have been a huge number of dibaryon predictions in the past. The oldest one dates back to 1964, when based on SU(6) symmetry considerations, Dyson and Xuong [12] [11,[53][54][55][56][57] are compared to those from theoretical calculations [52,58], starting from the theoretical wave function and including isospin breaking effects. They are also compared to the values expected from pure isospin recoupling of the various channels.…”
Section: Electromagnetic Excitation Of (2380)mentioning
confidence: 99%